The Effect of The Coastal District of Social Perspectives In The Kampung Nelayan Indah Belawan Medan - B O Y Marpaung; Mahmudatun Nisa Daulay (International Journal of Architecture and Urbanism, 2018)
A person's views or beliefs affect space in the coastal environment. The settlement in the Kampung Nelayan Indah Belawan Medan was built because of the government's assumption in building the settlement and spatial planning in the coastal area. The space formed in the settlement is adapted to the pattern of community activities that occupy it to facilitate local people in doing their work outside the room. The coastal areas also affect the social perspectives of people living in settlements. Social views arise because of age, education, socioeconomic, socio-cultural, counseling. Researchers use quantitative methods in analyzing the public perception and social view of the reality of space formed in the Kampung Nelayan Indah Belawan Medan. While the qualitative method used to analyze the factors affect the different views between occupants.